Dietary habits and their effects on the health of the population in Almashroaa ALsabaa neighborhood in Lattakia - خدام , منذر; عبود , هشام (Latakia University Journal -Biological Sciences Series, 2021)
The research aimes to identify the Dietary habits of a sample of families in the Almashroaa ALsabaa neighborhood, Almashroaa ALsabaa is one of the neighborhoods of Lattakia, which has all the elements for conducting such studies. A random sample of 55 families are selected, which are questioned according to a form designed for this purpose. Its data includes the social, educational, economic and cultural characteristics of the individuals of the studied sample and the frequency of their consumption of different foods within a month. The results showed that the sources of protein in the sample families mostly depende on legumes, followed by eggs, then milk and its derivatives, then white meat and finally Red meat. It is also evident that the food of most of the sample members depende on carbohydrates and fats, as it contains less protein from animal sources, as these families depend for their food on complex meals of grains, legumes and some vegetables, and they consume fewer amounts of protein-rich animal foods, due to the high prices. The research also concluds that there are some negative dietary habits for the surveyed families, such as the absence of breakfast or being limited to one meal throughout the day, drinking water with lunch, excessive eating fast food, salty foods and spices, excessive sweets and chocolate, and drinking tea and soft drinks with or after the main meals directly. The research recommends the necessity of the availability of specialized and comprehensive studies that simulate the health status of the population, and the urgent need to educate families to avoid bad eating habits through audio-visual media, and to guide them to adopt a balanced diet to reduce health problems caused by malnutrition.